Exploring pre-service teachers’ self-efficacy in practicing sustainable gender equality: a case study from Morocco - Delbouh, Ahmed; El Ghordaf, Jalila; Taia, Abdallah; Oufroukhi, Mohamed; Haddad, Sabah (Frontiers in Education, 2025)
IntroductionTeachers’ self-efficacy in gender-responsive teaching plays a crucial role in fostering future generations attuned to gender equality. However, there is limited research on the effectiveness of foundational teacher training in Morocco in addressing gender equality. This study investigates the self-efficacy of pre-service teachers in implementing gender-responsive practices and examines how their social backgrounds influence their perspectives, with a focus on gender-based differences.MethodsA quantitative survey approach was employed, using an adapted version of the Teacher Efficacy for Gender Equality Practice (TEGEP) measurement tool. The online survey was distributed to pre-service teachers in regional teacher training centers across five Moroccanregions. A total of 516 trainees participated in the study.ResultsThe findings revealed: (a) significant gender disparities in family culture, household task perceptions, and traditional roles; (b) progress in fostering gender-equal learning environments; (c) a general deficiency in gender awareness and knowledge among both male and female trainees; (d) a greater readiness among female trainees to implement gender responsive teaching methods and develop gender-equitable attitudes, indicating a stronger awareness of gender equality among women.DiscussionWhile progress has been made in promoting gender equality in Moroccan teacher training programs, challenges remain in addressing ingrained cultural perceptions and enhancing gender awareness. The study faced limitations related to electronic data collection, including variability in participant numbers across training centers and potential discrepancies in survey question interpretation. Based on the findings, recommendations are proposed to improve gender-responsive teaching practices in teacher training programs.